Psychometrical analysis of Purpose in Life Test in school students from Arequipa City (Peru) - Huamani Cahua, Julio Cesar (2018)
In this article, we present the psychometrical analysis of the Purpose in Life Test ofCrumbaugh y Maholick (1969) in a sample of high school students from Arequipa City (Peru). We selected a non-probabilistic sample of 872 students of 4th and 5th grade of five public high schoolsinto the city, who were tested by the Spanish version of Purpose in Life Test (Noblejas, 1994). We analyze the construct validity and reliability of the test through the exploratory and confirmatory factor analysisand the Cronbach’s Alfa Test. The results confirm the four factors structure reported by Noblejas (2000), but the items 4 and 19 were eliminated and the reliability indexes are higher than 0.7 for the total punctuationand each factor.